MOTIVASI BELAJAR IPA FISIKA DALAM MASA PANDEMI COVID-19 SISWA SMP DI PEKANBARU - Arif Septian; Zulirfan Zulirfan; Fakhruddin Z Fakhruddin Z (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The Covid-19 pandemic has made the implementation of learningunable to take place normally. Learning that is carried out online from home hasweaknesses that have an impact on students, namely students find it difficult tounderstand the subject matter, students' absorption of lessons is low and students'motivation to learn decreases. This study aims to determine the motivation to learnScience Physics for junior high school students during the Covid-19 pandemic inPekanbaru and the differences in motivation for learning Science Physics for juniorhigh school students during the Covid 19 pandemic between boys and girls inPekanbaru. The type of research is descriptive research with survey method. Thesubjects in this study were grade VIII junior high school students in five public schoolsand four private schools in Pekanbaru. The number of respondents from this study were204 students with 86 male students and 118 female students. The data collectiontechnique in this study was a questionnaire technique. The questionnaire was given tothe research sample via theplatform google form. The results showed that themotivation to learn Science Physics for junior high school students during the Covid-19pandemic in Pekanbaru was in the high category. The motivation to learn SciencePhysics between male and female students showed no significant difference in scores,and did not show that there was no significant difference between the motivation scoresof male and female students.Key Words: Students’ Motivation, The Covid-19 Pandemic, Online Learning.